Integrating Ecotheology into Islamic Religious Education: A Systematic Literature Review on Students’ Spiritual, Social, and Cognitive Character Development - Sapitri, Elfira Yunita; Hamami, Tasman; Muttakin, Khaerul (DAYAH: Journal of Islamic Education, 2025)
The global ecological crisis demands an educational response that is not only technical but also ethical and spiritual. This study systematically reviews the integration of ecotheology into Islamic Religious Education (IRE) and synthesizes evidence on its effects on students’ spiritual, social, and cognitive character development. Using a Systematic Literature Review design guided by PRISMA 2020, we searched Scopus and Google Scholar for peer-reviewed studies published between 2020 and 2025 using Boolean combinations of eco-theology/Islamic environmental ethics, Islamic education/IRE, and character-related outcomes. After identification, deduplication, screening, and full-text eligibility assessment, 33 studies met the inclusion criteria and were analyzed through thematic narrative synthesis. The findings show that ecotheology is integrated into IRE through three main pathways: (1) curriculum strengthening (learning objectives, content, and materials grounded in Islamic ecological principles), (2) contextual–reflective pedagogies (including problem-based, experiential, and project-based learning), and (3) authentic assessment (e.g., reflective journals, portfolios, and behavior-based observation). Across the reviewed literature, ecotheology integration tends to enhance students’ spiritual awareness, strengthen socio-ecological responsibility and solidarity, and foster critical and reflective thinking about sustainability. However, a key limitation across studies is the lack of standardized learning-outcome indicators and validated evaluation instruments for ecotheology within IRE. This review highlights the need for a structured pedagogical framework and an assessment system to support consistent implementation and measurable outcomes in ecotheology-oriented Islamic education. Abstrak Krisis ekologi global menuntut respons pendidikan yang tidak hanya bersifat teknis, tetapi juga etis dan spiritual. Penelitian ini menyajikan tinjauan literatur sistematis mengenai integrasi ekoteologi dalam Pendidikan Agama Islam (PAI) serta mensintesis temuan-temuan empiris terkait dampaknya terhadap pengembangan karakter spiritual, sosial, dan kognitif peserta didik. Penelitian menggunakan desain Systematic Literature Review (SLR) dengan panduan PRISMA 2020. Proses penelusuran dilakukan melalui basis data Scopus dan Google Scholar terhadap artikel ilmiah yang dipublikasikan antara tahun 2020 hingga 2025, menggunakan kombinasi Boolean yang mencakup konsep ekoteologi/etika lingkungan Islam, pendidikan Islam/PAI, serta dimensi karakter. Setelah melalui tahap identifikasi, eliminasi duplikasi, penyaringan, dan evaluasi kelayakan teks penuh, sebanyak 33 artikel memenuhi kriteria inklusi dan dianalisis melalui pendekatan sintesis naratif tematik. Hasil kajian menunjukkan bahwa integrasi ekoteologi dalam PAI berlangsung melalui tiga jalur utama: (1) penguatan kurikulum (perumusan tujuan pembelajaran, materi, dan konten berbasis prinsip ekologi Islam), (2) penerapan pedagogi kontekstual-reflektif (termasuk problem-based learning, experiential learning, dan project-based learning), serta (3) penggunaan asesmen autentik (seperti jurnal reflektif, portofolio, dan observasi perilaku). Secara umum, integrasi ekoteologi berkontribusi pada peningkatan kesadaran spiritual peserta didik, penguatan tanggung jawab sosial-ekologis, serta pengembangan kemampuan berpikir kritis dan reflektif terhadap isu keberlanjutan. Namun demikian, keterbatasan utama yang teridentifikasi adalah belum tersedianya indikator capaian pembelajaran yang terstandar serta instrumen evaluasi yang tervalidasi untuk ekoteologi dalam PAI. Kajian ini menegaskan urgensi pengembangan kerangka pedagogis dan sistem asesmen yang sistematis guna mendukung implementasi yang konsisten dan terukur dalam pendidikan Islam berbasis ekoteologi.